Aluda Ketelauri - Donald Rayfield (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2011)
The purpose of the section Georgian Literature in English Translations in the Kartvelologist is to provide the English- language reader with excerpts of best specimens of Georgian literature with a parallel English translation. The Editorial Staff hopes that in this way the interested reader will form an idea of Georgian poetry, belles-lettres and historical literature. At the same time, the reader interested in studying the Georgian language will be enabled to acquaint him/herself with excerpts of the best specimens of Georgian literature in the original with parallel English translations. Presented in this issue of the Kartvelologist is the first chapter of “Aluda Ketelauri”, a well-known poem by the classic of Georgian poetry Vazha Pshavela (the same Luka Razikashvili, 1861-1915) translated by the English Kartvelologist Donald Rayfield (the translation was published in Tbilisi, in 1981 by “Ganatleba”: Vazha Pshavela, “Three Poems”). The compositionally completed story of the first chapter of this poem depicts the lofty ideal of humaneness, respect for man’s personal dignity in overcoming religious and national confrontation, rising of a person’s free spiritual emotion above the traditional norms and customs of enmity between human beings. The Editor